The warrior [videorecording (DVD)] - Marianelli, Dario (Miramax Home Entertainment, 2006)
"In feudal India, a warrior (Khan) who renounces his role as the longitme enforcer to a local lord becomes the prey in a murderous hunt through the Himalayan mountains"--IMDb.